Effectiveness of low dose versus high dose oxytocin regimen for induction of labour - Gupta, Paridhi; Chawla, Indu; Gupta, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
ABSTRACT Background: Induction of labour is an indispensable part of modern obstetrics and certainly one of the most frequently performed obstetric procedure in the world. Oxytocin, being the most common inducing agent with multiple protocols being practiced, further research is required for the establishment of better protocol with optimal maternal and neonatal outcomes. Methods: Randomized comparative study including 100 term nulliparous women (randomized into high dose, group-I and low dose, group-II with 50 patients in each group) was done. High dose regimen was started with 4mu/min with increment of 4mu/min up to a maximum of 32mu/min and low dose regimen was started with 2mu/min with increment of 2mu/min up to a maximum of 32mu/min. Induction to delivery interval was the primary outcome. Secondary outcomes noted were rate of caesarean section, tachysytole with or without fetal distress, failed induction, maternal outcomes like need for instrumental vaginal delivery, PPH and choriamnionitis, neonatal outcomes like NICU admission, umbilical cord pH and apgar score. Results: There was significant reduction seen in induction to delivery interval among those induced with high dose oxytocin regimen. It was found to be 6.96±3.77 hours in group-I and 9.05±4.65 hours in group-II (p value 0.034). Though incidence of tachysystole was more in high dose regimen, it was not statistically significant. No significant difference was seen in secondary outcomes. Conclusions: On the basis of present study, high dose oxytocin regimen can be considered for induction of labour as it has same effects as that of low dose regimen with lesser induction to delivery interval.